2000
DOI: 10.1359/jbmr.2000.15.12.2513
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Metabolism of Estradiol Conditions Postmenopausal Bone Density and Bone Loss

Abstract: Because lifelong exposure to estrogen is a strong determinant of bone mass, we asked whether metabolic conversion of estrogen to either inactive or active metabolites would reflect postmenopausal bone mineral density (BMD) and rate of bone loss. Biochemical markers of inactive estrogen metabolites, urinary 2-hydroxyestrogen (2OHE 1 ) and 2-methoxyestrogen (2MeOE 1 ), and active metabolites, urinary 16␣-hydroxyestrone (16␣OHE 1 ), estradiol (E 2 ), and estriol (E 3 ), were determined in 71 untreated, healthy po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 57 publications
(67 reference statements)
1
48
1
Order By: Relevance
“…Disorders of estrogen metabolism have been implicated in the etiology of certain estrogen-dependent conditions, such as breast, endometrial, and ovarian cancers (5-7) and, recently, osteoporosis (8). For instance, it has been reported that women with increased 16␣-hydroxylation, as indicated by a low ratio of 2-hydroxyestrone (2OHE 1 ) to 16␣-hydroxyestrone (16␣OHE 1 ), have a high risk of breast cancer (5,9), most likely because of a relatively higher estrogenic state.…”
Section: Introductionmentioning
confidence: 99%
“…Disorders of estrogen metabolism have been implicated in the etiology of certain estrogen-dependent conditions, such as breast, endometrial, and ovarian cancers (5-7) and, recently, osteoporosis (8). For instance, it has been reported that women with increased 16␣-hydroxylation, as indicated by a low ratio of 2-hydroxyestrone (2OHE 1 ) to 16␣-hydroxyestrone (16␣OHE 1 ), have a high risk of breast cancer (5,9), most likely because of a relatively higher estrogenic state.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, African-American women, who had a greater bone mass and lower risk for developing osteoporosis compared with European-American women, have been reported to have a higher urinary 16 -OHE 1 /2-OHE 1 ratio (Cauley et al 1994, Taioli et al 1996. More recent data suggested that women in the lowest quartile of urinary 2-OHE 1 / 16 -OHE 1 appeared to be protected from early postmenopausal bone loss (Leelawattana et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that hormones and exercise interact to influence bone adaptations, and thus raise E 3 level related to increased BMD following exercise in female athletes. For example, serum E 2 , cortisol, PTH and T 3 levels in the athlete group were higher than those of the controls, and the major finding of this study was that increased radius BMD (K<0.05) and calcaneus BMD (K<0.01, P<0.05) were significantly and positively related to serum E 3 (K<0.01, P<0.01) concentrations [10][11][12] . Therefore, a clear understanding the interaction suggested by the present data between E 3 concentration and the adaptation of bone to exercise is important, and provides an interaction through which the estrogen receptors involved in the early response of bone cells might increase their responsiveness to loading [11,12] .…”
Section: Discussionmentioning
confidence: 48%
“…Consequently, lifelong physical exercise is recommended to optimize health-related benefits [2][3][4][5][6][7][8] . And the influence of physical activity and exercise training on BMD in females previously has been assessed in cross-sectional, retrospective longitudinal and controlled trial studies [3][4][5][6][7][8][9][10][11][12][13] . Even though no relationship about growth hormone and BMD was found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation